MOSQUE MANAGEMENT RESPONSE TO PRODUCTIVE WAQF - Suhairi, Suhairi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2019)
Questions in this study are: What is the response of the board to the management of mosque-based productive waqf? The purpose of this study is to elaborate the management's response to the management of productive mosque-based waqf. The research conducted wasfield research, in the form of a mosque that met the criteria used as a research location. Mosque criteria are those that have the potential of managing a mosque-based productive waqf. Data collection is done through interviews. From the four mosques studied, the management's response had differences. The response of the mosque management and or the foundation, one mosque, the Babussalam Pekalongan East Lampung Mosque, the management objected if it was built in the front yard of the shop. The reason stated, the existence of the mosque for worship, not for business. While the management of the other three mosques agreed and strongly agreed that a mosque-based productive waqf management would be carried out by building shops in its front yard. Keywords: Productive Waqf, Nazhir, and Empowerment of Waqf Land